Literature Revitalizes the Past: Historicizing John Dryden’s Literary Contributions - Afshan, Sahar; Ali, Shahwar (Journal of Research in Humanities, 2023)
Literature revitalizes the past by presenting a blended picture of the real and the imaginative, with Author’s unique vision and experience. A literary text is thus an artistic representation of the culture in which it is written implying that a work of art is indispensable from the historical background of its age. In recent days most students and teachers consider it useless to study the writers of the bygone era which poses a severe threat to the perseverance of the tradition of Literary Classics. Hence, the study aims to revitalize the importance of studying literature of past centuries in present times by historicizing the literary contributions of John Dryden, a 17th-century poet. The approach of historicization is used to explain the socio-political environment in the 17th century and speculate how this environment has shaped the thematic content and style of Dryden’s works.